SKY IN THE CIVILIZATION OF ANCIENT IRAQ - Ahmed, Abdullah; Aziz Al-Zebari, Aziz (Humanities Journal of University of Zakho, 2025)
Researches about the ancient civilization of Iraq has a great importance because it carries a hight place in an ancient world, as for the first time writing, planting, religious beliefs, and the early democratic system has appeared in ancient Iraq…etc. many cultures appeared before the history which caused its development. Ancient Iraq as a country and a system has looked for cosmic phenomena because human lives were filled with risks and natural disasters. Humans lived for a long time, thus, during their lives they tried to know their origins and destiny. Their understanding was limited and their observations were focused on what was around them. They believed in the existence of strange creatures. These creatures caused illness, hunger, fear, and death. In fear of death and dangerous incidents, they sought refuge in the mercy of gods in order to earn their approval. In beliefs of ancient Iraq, the sky had a crucial importance, because it was the residence of powerful gods, the symbol of rise, a centre of many activities, and was directly connected to gods. Obeying decisions of gods of the sky caused the occurrence of blessings, while disobeying them caused the punishment because it was the source of many disasters, the cause of fear, death, and destructions. The myths of Sumerian and Akkadian were about many subjects, including the organization of the universe, the birth of the gods, the curse and love, the rivalry of the gods, their plans, their holiness, and their curses. They also addressed the life after death, stories, and heroic deeds. In the creation of Babylon, the story of Gilgamesh, and the story of the flood, the sky played an important role, particularly the god Anu because of its position in the minds and hearts of the people of ancient Iraq.